Host identity impacts rhizosphere fungal communities associated with three alpine plant species - Becklin, Katie M.; Hertweck, Kate L.; Jumpponen, Ari M. (My University, 2012)
Fungal diversity and composition are still relatively unknown in many ecosystems; however, host identity and environmental conditions are hypothesized to influence fungal community assembly. To test these hypotheses we characterized the richness, diversity, and composition of rhizosphere fungi colonizing three alpine plant species, Taraxacum ceratophorum, Taraxacum officinale, and Polemonium viscosum. Roots were collected from open meadow and willow understory habitats at treeline on Pennsylvania Mountain, Colorado, USA. Fungal small subunit ribosomal DNA was sequenced using fungal-specific primers, sample-specific DNA tags, and 454 pyrosequencing. We classified operational taxonomic units (OTUs) as arbuscular mycorrhizal (AMF) or non-arbuscular mycorrhizal (non-AMF) fungi, then tested whether habitat or host identity influenced these fungal communities. Approximately 14% of the sequences represented AMF taxa (44 OTUs) with the majority belonging to Glomus group A and B. NONAMF sequences represented 186 OTUs belonging to Ascomycota (58%), Basidiomycota (26%), Zygomycota (14%), and Chytridiomycota (2%) phyla. Total AMF and non-AMF richness were similar between habitats, but varied among host species. AMF richness and diversity per root sample also varied among host species and were highest in T. ceratophorum compared to T. officinale and P. viscosum. In contrast, non-AMF richness and diversity per root sample were similar among host species except in the willow understory where diversity was reduced in T. officinale. Fungal community composition was influenced by host identity, but not habitat. Specifically, T. officinale hosted a different AMF community than T. ceratophorum and P. viscosum, while P. viscosum hosted a different non-AMF community than T. ceratophorum and T. officinale. Our results suggest that host identity has a stronger effect on rhizosphere fungi than habitat. Furthermore, although host identity influenced both AMF and non-AMF this effect was stronger for the mutualistic AMF community.
Keywords: Host identity; Rhizosphere fungal communities